Characterization and Interpretation of Dedicated Reservoir Interval: A 2D Seismic Structural Approach - Idan, Rami M.; Al-Khazraji, Omar (Iraqi Journal of Science, 2024)
In the present study, three different depth conversion methods have been used with varying equations at Mishrif Formation to determine the best method to produce better, more realistic and accurate interpretation results and to reduce the risk of future petroleum production wells drilling. Three horizons were picked (Tanuma, Mishrif and Rumaila) and converted into a two-way time grid surface. In addition, the velocity parameters (instantaneous velocity and rate of velocity change with depth) were computed and converted to the form grid surface from the well data, showing lateral velocity variation. Among the three models carried out, the Model 1 is considered the most accurate depth conversion method in this region according to the results of the geostatistical analysis. This method gave fewer errors and mistakes between actual and predicted depth with the best intra-extrapolation technique at all directions away from the well area with a standard deviation value of 13.2, and the standard deviation values of 13.6 and 13.9 for models 2 and 3, respectively.